2015
DOI: 10.1080/07448481.2015.1060596
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Perceptions of Professor/Instructor Bullying: Questionnaire Development and Psychometric Properties

Abstract: Objective This study developed and examined the psychometric properties of a newly formed measure designed to assess professor/instructor bullying, as well as teacher bullying occurring prior to college. Additionally, prevalence of instructor bullying and characteristics related to victims of instructor bullying were examined. Participants Participants were 337 college students recruited in 2012 from a northeastern university. Methods An online questionnaire was administered to college students. A split-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
2
18
3
2
Order By: Relevance
“…In the study by Chapell et al (2004) among 1025 undergraduate students in a U.S. university, the number of students who reported having been bullied by a college teacher occasionally was 4.2%, and very frequently by only 0.5% of the students. Quite similarly, Marraccini et al (2015) found that of the 337 students recruited from a U.S. college, 3.1% reported having been bullied by a teacher/researcher occasionally and 0.9% very frequently. In a study conducted among 5698 higher education students in Finland, students also reported less bullying from teaching/research personnel than from their fellow students (Lavikainen 2010).…”
Section: Experiences Of Bullying By University Personnelmentioning
confidence: 92%
See 3 more Smart Citations
“…In the study by Chapell et al (2004) among 1025 undergraduate students in a U.S. university, the number of students who reported having been bullied by a college teacher occasionally was 4.2%, and very frequently by only 0.5% of the students. Quite similarly, Marraccini et al (2015) found that of the 337 students recruited from a U.S. college, 3.1% reported having been bullied by a teacher/researcher occasionally and 0.9% very frequently. In a study conducted among 5698 higher education students in Finland, students also reported less bullying from teaching/research personnel than from their fellow students (Lavikainen 2010).…”
Section: Experiences Of Bullying By University Personnelmentioning
confidence: 92%
“…Occurrence rates of students' experiences of being bullied by university personnel are not commonly reported, however, studies from the USA, Finland, and the United Kingdom indicate this kind of bullying exists (Chapell et al 2004;Cooper et al 2011;Lavikainen 2010;Marraccini et al 2015;NUS 2008;Sinkkonen et al 2014). In the study by Chapell et al (2004) among 1025 undergraduate students in a U.S. university, the number of students who reported having been bullied by a college teacher occasionally was 4.2%, and very frequently by only 0.5% of the students.…”
Section: Experiences Of Bullying By University Personnelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently, with emphasis that bullying does not disappear with humans' age, there is more and more interest in bullying existence in higher education, by recognizing it as a sensitive and still unsolved problem (Kyriacou, Mylonakou-Keke and Stephens, 2016). In this context, though recognizing the lack of researches (Lund and Ross, 2016), bullying is examined by analysing both the relationship between lecturers and students, and employees' relationship, and analysing the relationship between students (Marraccini, Weyandt and Rossi, 2015;Perry and Blincoe, 2015;Sinkkonen, Puhakka and Meriläinen, 2014;Serinkan et al, 2013;etc.). These researches can be performed by using different measures, such as questionnaires, interviews, diaries, observations that rely on different informants (Van Noorden et al, 2015).…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%